2009
DOI: 10.1074/jbc.m109.046805
|View full text |Cite
|
Sign up to set email alerts
|

iso-Migrastatin, Migrastatin, and Dorrigocin Production in Streptomyces platensis NRRL 18993 Is Governed by a Single Biosynthetic Machinery Featuring an Acyltransferase-less Type I Polyketide Synthase

Abstract: iso-Migrastatin and related glutarimide-containing polyketides are potent inhibitors of tumor cell migration and their implied potential as antimetastatic agents for human cancers has garnered significant attention. Genome scanning of Streptomyces platensis NRRL 18993 unveiled two candidate gene clusters (088D and mgs); each encodes acyltransferase-less type I polyketide synthases commensurate with iso-migrastatin biosynthesis. Both clusters were inactivated by -RED-mediated PCR-targeting mutagenesis in S. pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 51 publications
3
84
0
2
Order By: Relevance
“…Three of these additional clades appear to resolve different substrate specificities than those reported previously (21). The clade named "double-bond 3" (DB3) grouped the domains RhiKS14 and MgsKS2, both of which receive olefinic substrates that are subject to ring formation by Michael addition-dependent processes (22). The two other clades directly reflect the addition of HR-MS and tandem MS spectra of the crude extracts of each of T. turnerae wild type (Upper) and region 2 mutant, AH02 (Lower).…”
Section: Evolutionary Rationale Supports the Trtdef Pathway Role In Tmentioning
confidence: 93%
“…Three of these additional clades appear to resolve different substrate specificities than those reported previously (21). The clade named "double-bond 3" (DB3) grouped the domains RhiKS14 and MgsKS2, both of which receive olefinic substrates that are subject to ring formation by Michael addition-dependent processes (22). The two other clades directly reflect the addition of HR-MS and tandem MS spectra of the crude extracts of each of T. turnerae wild type (Upper) and region 2 mutant, AH02 (Lower).…”
Section: Evolutionary Rationale Supports the Trtdef Pathway Role In Tmentioning
confidence: 93%
“…Recently, the AT1 domain of KirC1, another homolog of OzmM-AT1 involved in kirromycin biosynthesis, was suggested to be inactive based on bioinformatic analysis (5). Another publication about the migrastatin biosynthetic gene cluster also demonstrated that MgsB may serve as a cryptic acyltransferase, whereas MgsH may act as the sole AT for iso-MGS biosynthesis because the ⌬mgsB gene mutant is still capable of producing iso-MGS (48). Here we present the in vivo data to show that these trans-AT domains with the catalytic Ser (amino acid residue 81) and His (amino acid residue 182) (numbering corresponding to OzmM-AT1) but with mutations at another two highly conserved amino acids, His (amino acid residue 80) and Arg (amino acid residue 106), may be inactive.…”
Section: Discussionmentioning
confidence: 99%
“…The scm PKS gene cluster contains homologous genes of all eight genes in the migrastatin PKS gene cluster in Streptomyces platensis NRRL 18993 (38). The migrastatin PKS gene cluster is an AT-less type I PKS gene cluster, which is involved in migrastatin biosynthesis.…”
Section: Alignment Of Schppt and Schacps With Known Pptases Showed Thmentioning
confidence: 99%